Determinants of tobacco smoking among rural-to-urban migrant workers: a cross-sectional survey in Shanghai - Liu, Yao (BMC Public Health, 2015)
BACKGROUND: Although there are several studies to investigate the smoking behaviors among rural-to-urban Chinese migrants, no study has focused individually on this population in Shanghai. This study was performed to estimate the prevalence and identify the determinants of tobacco smoking among rural-to-urban migrants in Shanghai. METHODS: In this cross-sectional study, multi-stage quota sampling was used to select 5,856 rural-to-urban migrants aged 18 years or older from seven districts in Shanghai between July and October 2012. A structured questionnaire was administered to assess smoking knowledge, attitude, behavior and demographic characteristics. Mental health was assessed by the self-reported SCL-90. Multiple logistic regression analysis was used to determine the risk factors of smoking behavior. RESULTS: A total of 5,380 of the 5,856 migrants enrolled completed the questionnaire, among whom 45.0% of male and 2.0% of female participants reported current smoking. Multivariate analysis revealed current smoking in female migrants to be significantly associated with working at construction (OR, 8.08; 95% CI, 1.80-36.28), hotels/restaurants (OR, 5.06; 95% CI, 1.68-15.27), entertainment sector (OR, 6.79; 95% CI, 2.51-18.42), with monthly income > 3500 yuan (OR, 2.69; 95% CI, 1.21-5.98), number of migratory cities of 2 (OR, 2.39; 95% CI, 1.23-4.65), and SCL-90 total score > 160 (OR, 2.03; 95% CI, 1.03-3.98), while the male migrants working at construction (OR, 1.30; 95% CI, 1.04-1.62), entertainment sector (OR, 1.86; 95% CI, 1.36-2.56), being divorced/widowed (OR, 2.20; 95% CI, 1.02-4.74), with duration of migration of 4 or more than 4 years (OR, 1.42; 95% CI, 1.06-1.91), number of migratory cities of 3 or more than 3 (OR, 1.42; 95% CI, 1.13-1.80), and SCL-90 total score > 160 (OR,1.39; 95% CI, 1.07-1.79) showed an excess smoking prevalence. CONCLUSION: Migration lifestyle and mental status were associated with current smoking behaviors. The identifications of risk factors for current smoking may help to target health promotion interventions.